(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
This article examines the transformation of tax accounting in the digital economy and the methodological foundations for its automation. The study analyzes the use of digital technologies in tax accounting, including electronic tax systems, cloud platforms, Big Data, and artificial intelligence. Particular attention is paid to improving tax administration, automating tax reporting processes, increasing the efficiency of tax control, and reducing the impact of the human factor. As a result of the research, methodological approaches for the digital transformation of tax accounting are developed and practical recommendations for their implementation are proposed.